Analisis Penerapan Akuntansi Syariah Pada Pembiayaan Murabahah PT. Bank Syariah Indonesia Dengan Mengacu Pada PSAK 102 - Charla Gutri Santika; Ferdy Jumansyah; Irma Yuniza; Lisa Nuraini (Jurnal Riset Akuntansi, 2024)
Sharia banking in Indonesia is experiencing rapid development by offering products that are different from conventional banking. One of Bank Syariah Indonesia's (BSI) flagship products that customers are interested in is the murabahah financing contract. Murabahah is the activity of buying and selling goods with a selling price equal to the acquisition price plus an agreed profit. The seller must disclose the purchase price of the goods to the buyer. Murabahah transactions at BSI are subject to PSAK No. 102. This PSAK is a guideline in the process of recognizing, measuring, submitting and presenting financial reports. This research aims to analyze the suitability of BSI's murabahah financing policy with PSAK 102. The data used is secondary data from books, citations, articles, journals, as well as BSI's financial reports and annual reports. The research results show that the application of sharia accounting based on PSAK 102 in murabahah financing at BSI is fully appropriate. This applies at the time of recognition and measurement, presentation and distribution. In conclusion, BSI has implemented PSAK 102 well in murabahah financing. This shows BSI's commitment to running a transparent and accountable sharia business.